Case analysis of Donald Trump's 2025 tax rate hike on cooperation with Indonesia and its impact on the global economy - Hutapea, Inggrid Brigita Vinsensa (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: The phenomenon of Donald Trump raising tariffs on several trading partner countries is causing conflicting political and economic situations internationally. This has put several developing countries under pressure, including Indonesia itself. The focus of this research is to understand how Indonesian Micro, Small, and Medium Enterprises (MSMEs) maintain their price competitiveness amid these tariff policy changes, as well as to analyse the political communication strategies implemented by Indonesia in addressing these challenges on the international stage. Methods: This research uses a qualitative method based on literature review, as well as analysis techniques that use literature review and discourse analysis of official statements, policies, and public responses. Findings: The results of the analysis lead to the conclusion that this research focuses on key political communication strategies that not only involve negotiations at the government level but also build positive narratives in the international public sphere to attract sympathy and cooperation from other countries. The analysis shows that Indonesia, through its political communication strategy, seeks to strengthen the image of MSMEs in the global market, build new economic alliances, and expand its economic diplomacy network to reduce dependence on markets that impose high tariffs. Maintaining economic balance depends on cooperation that involves strategic and collaborative communication. Conclusions: Thus, this study concludes that in the era of new protectionism, the success of developing countries in maintaining their economic position depends heavily on their ability to conduct strong economic diplomacy, supported by effective and adaptive political communication strategies in response to global dynamics. This strategy not only involves negotiations at the government level but also building a positive narrative in the international public sphere to attract sympathy and cooperation from other countries. Novelty/Originality of this article: The novelty of this article lies in its analysis of political communication and economic diplomacy in understanding the impact of international tariff policies on developing countries, particularly in the context of global power imbalances.